Glass recycling in the production of low-temperature stoneware tiles. (1st October 2018) - Lassinantti Gualtieri, Magdalena; Mugoni, Consuelo; Guandalini, Sara; Cattini, Andrea; Mazzini, Denia; Alboni, Claudio; Siligardi, Cristina
Abstract: The current study deals with the development of low-temperature stoneware tiles with boron-rich waste glass as sintering promotor in a modified triaxial ceramic body. The obtained results are part of a larger project financed by the Italian region of Emilia Romagna and aiming at developing novel formulations for sustainable ceramic products classified as porcelain stoneware. We successfully obtained highly vitrified ceramic tiles (BIa class) at a firing temperature almost 140 °C lower than that normally applied for this product by modifying a traditional triaxial composition and including waste glass. The ecological sustainability was thus improved by lower emissions and substitution of natural raw materials with secondary ones. Pilot scale trials confirmed full adaptability to existing powder processing routes. The microstructure and the temperature-induced phase evolution were analyzed by scanning electron microscopy (SEM) and quantitative phase analyses using X-ray powder diffraction (XRPD) and the Rietveld method. It will be shown that the triaxial body minerals are highly reactive in the boron-rich viscous melt leading to eutectic melting and recrystallization. The high reactivity renders this particular ceramic system flexible in terms of liquid phase composition and post-firing crystal assemblages and is therefore suitable as a base system for design of sustainable ceramic products. Graphical abstract: Highlights: BIa-classified tiles were made with boron-rich waste glass as sintering promotor. The firing temperature was lowered by 140 °C when waste glass was included. Pilot scale trials confirmed full adaptability to existing powder processing routes. The residual stress was lower compared to traditional porcelain stoneware. High reactivity renders this system a good basis for design of eco-sustainable tiles.